REDUCING SOCIAL INEQUALITY THROUGH MICRO-INCLUSIVE ECONOMIC POLICIES: A CASE STUDY FROM DEVELOPING COUNTRIES - Loso Judijanto; Hadenan Towpek (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the effectiveness of micro-inclusive economic policies in addressing social inequality in developing countries. Social inequality often arises due to disparities in access to economic resources, education, and employment, thereby hindering overall community welfare. Through a case study approach, this research explores various policies that focus on empowering small and medium enterprises (SMEs), providing access to credit for vulnerable groups, and training programmes to improve community capacity. The results of the study indicate that micro-inclusive policies have great potential to reduce social inequality and provide opportunities for marginalised groups to contribute more actively to economic activities. However, the implementation of these policies faces challenges such as a lack of synergy between various stakeholders, limited resources, and obstacles in effective policy monitoring. Therefore, this study emphasises the importance of a holistic approach involving the government, the private sector, and civil society in supporting inclusive policies. In addition, policy adaptation to the local context and the use of community-based technology are important strategies for promoting more significant positive impacts. Overall, this study concludes that micro-inclusive economic policies can be an effective tool for reducing social inequality, provided that they are accompanied by transparent and accountable implementation processes and continuous evaluation. The policy recommendations designed from the results of this study can serve as a guide for developing countries to create more equitable and inclusive economic development.